2019
DOI: 10.1055/s-0039-1695038
|View full text |Cite
|
Sign up to set email alerts
|

Preoperatively Identified Sarcopenia Leads to Increased Postoperative Complications, Hospital and ICU Length of Stay in Autologous Microsurgical Breast Reconstruction

Abstract: Background Sarcopenia is a condition characterized by the loss of skeletal muscle mass and strength. Recently, there has been a tremendous amount of research into the prognostic value of sarcopenia in surgical outcomes. The purpose of this study was to compare postoperative outcomes in free flap breast reconstruction in patients with and without sarcopenia. Methods One hundred three patients who underwent autologous breast reconstruction from 2013 to 2016 were studied. The cross-sectional area (CSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 23 publications
1
20
0
2
Order By: Relevance
“…The minimum threshold to define sarcopenia varies considerably between studies, methods, sex, and different populations. 1,3,[29][30][31][32]34,36 However, the thresholds we obtained via ROC analysis were comparable to HUAC values previously reported in the plastic surgery literature, 19,29 while also roughly paralleling use of the bottom quartile to define sarcopenia by some authors. 29 Notably, there was a high concordance with sarcopenia and other factors such as age, sex, and diabetes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The minimum threshold to define sarcopenia varies considerably between studies, methods, sex, and different populations. 1,3,[29][30][31][32]34,36 However, the thresholds we obtained via ROC analysis were comparable to HUAC values previously reported in the plastic surgery literature, 19,29 while also roughly paralleling use of the bottom quartile to define sarcopenia by some authors. 29 Notably, there was a high concordance with sarcopenia and other factors such as age, sex, and diabetes.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings concur with the strong consensus on sarcopenia's value as a prognostic indicator. 1,3,[29][30][31][32]34,36,37,62 Both the ellipse and traditional methods were concordant and accurate, predicting complications with an accuracy of 70 and 60%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are recognized preoperative patient-related factors that can affect flap outcomes, tissue oximetry monitoring can decrease free flap loss and improve salvage rate in the postoperative setting. 4,[11][12][13] A survey found that microsurgeons were more likely to immediately return to the operating room for a concerning tissue oximetry reading than an abnormal Doppler signal. 3 Other investigators have shown benefits of incorporating tissue oximetry in flap monitoring protocols as well.…”
Section: Discussionmentioning
confidence: 99%
“…1 Deep inferior epigastric perforator (DIEP) flaps were introduced 25 years ago 2 and have since become the preferred choice for breast reconstruction in autologous tissue reconstruction due to lower morbidity and faster recovery compared with transverse rectus abdominis musculocutaneous (TRAM) flaps. [3][4][5][6] DIEP flaps can be a favorable option for patients due to an abdominal tightening component with less abdominal wall morbidity at the donor site. 7 Evidence suggests autologous-based reconstruction has superior patient satisfaction postoperatively as well as improved aesthetic outcome and psychological well-being.…”
mentioning
confidence: 99%